2016
DOI: 10.5815/ijitcs.2016.01.04
|View full text |Cite
|
Sign up to set email alerts
|

Extraction of Root Words using Morphological Analyzer for Devanagari Script

Abstract: Abstract-In India, more than 300 million people use Devanagari script for documentation. In Devanagari script, Marathi and Hindi are mainly used as primary language of Maharashtra state and national language of India respectively. As compared with English script, Devanagari script is reach of morphemes. Thus the lemmatization of Devanagari script is quite complex than that of English script. There is lack of resources for Devanagari script such as WordNet, ontology representation, parsing the keywords and thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…In the literature review, the researcher found very few resources for stemming processing on the Gujarati language. So, it is an urgent need to develop a mature stemming algorithm which can help for several Indian languages including Gujarati, Marathi [44], Odia, and Pashto.…”
Section: Related Workmentioning
confidence: 99%
“…In the literature review, the researcher found very few resources for stemming processing on the Gujarati language. So, it is an urgent need to develop a mature stemming algorithm which can help for several Indian languages including Gujarati, Marathi [44], Odia, and Pashto.…”
Section: Related Workmentioning
confidence: 99%
“…Stemming can reduce dictionary size which is utilized as a part of different natural language processing applications, particularly for highly inflected languages. However, it is easy to extract root words by applying stemming algorithm for language like English [31]. The design of stemmers is language specific and requires some to significant linguistic expertise in the language, as well as the understanding of the needs for a spelling checker for that language [9].…”
Section: Spell Checkermentioning
confidence: 99%